HOW TO IMPROVE LISTENING SKILL? (Ustozlar uchun, 2024)
ABSTRACTThe theme of developing effective listening skills is an essential aspect of personal and professional growth. Effective listening is not merely the act of hearing; it encompasses the ability to comprehend, analyze, and respond to spoken information. An annotation on this theme could explore the following points.